City Government Intervention in Gampong Budgeting: Case Study in Banda Aceh, Indonesia - Ruzan, Muhammad Geubrika; Abdullah, Syukriy; Darwanis, Darwanis (Journal of Accounting Research, Organization and Economics, 2021)
Objective This study aims to explain the intervention of City Government in budgeting in Gampong1 by using agency theory in Banda Aceh.Design/methodology This study is qualitative approach, by collecting data through interviews officials and members of the Gampongs People Representative Council in 5 gam-pongs in Banda Aceh City, Head of sub-district, City Inspectorate, and representatives from the Gampong Community Empowerment Office. Questionnaires were distributed with a total of 363 respondents.Results The results showed that there was an intervention from City Government in the budgeting process in Gampong as a result of the existence of City Government authority as a coach and supervisor of the Gampong government. In addition, the results of the inspec-torate's examination also greatly influenced budgeting in the village the following year.Research Limitation/Implications The lack of literature and previous research on agency problems that occur in the village, the limited competence and lack of cooperation be-tween Keuchik and Tuha Peut Gampong (TPG) when asked for information through inter-views and questionnaires, and The lack of literature on the influence of personal conflict fac-tors (interpersonal) on agency problems.Novelty/Originality The results of this study are expected to be a reference material for academics to examine agency problems in the gampong.